Quilling Techniques and Inspiration - Jenkins, Jane (Tubridge Wells, England Search Press, 2003)
Jane Jenkins explains quilling techniques from closed loose coils to fringed flowers, with step-by-step photographs for clarity. She has designed a beautiful project to go with each technique so that new quillers can build their skills while producing quilled works of art. She shows how to make Art Nouveau and fantasy figures, Victorian fans, butterflies, candlestick holders and more. The beautiful, intricate and delicate filigreed patterns and pictures she creates are original and unique - and guaranteed to get you 'rolling'
Arts (Papercrafts)
The first published edition in 2016 are available at MPL-ZTN
1 2 13
Keywords: Paper crafts; Paper quillwork